1991
DOI: 10.1080/00268979100101921
|View full text |Cite
|
Sign up to set email alerts
|

Surface segregation of a binary liquid mixture as studied by metastable impact electron spectroscopy

Abstract: We have investigated the free liquid surface of a binary mixture of formamide and benzylalcohol using MIES (= metastable impact electron spectroscopy) and UPS. Whereas the latter samples information down to a depth of ~ 6A the method MIES is sensitive exclusively for the topmost molecular layer. The combination of both techniques allows us to determine the parameters of an exponential segregation profile. As expected from its smaller surface tension benzylalcohol is strongly enriched at the surface. The segreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

1992
1992
1997
1997

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
1
9
1
Order By: Relevance
“…The relative contribution to the mixture spectrum is always found to be higher than the value for the bulk composition, reaching a maximum of six times the bulk value near 10 vol % benzyl alcohol. This result is identical to the reported data of Morgner et al [13].…”
Section: Formamide and Benzyl Alcoholsupporting
confidence: 94%
See 3 more Smart Citations
“…The relative contribution to the mixture spectrum is always found to be higher than the value for the bulk composition, reaching a maximum of six times the bulk value near 10 vol % benzyl alcohol. This result is identical to the reported data of Morgner et al [13].…”
Section: Formamide and Benzyl Alcoholsupporting
confidence: 94%
“…It should be noted that there is no smooth variation of the overall position of the component spectra as a function of the bulk molar fraction, contrasting with the observations of the core level ionization bands reported by Siegbahn et al [9]. This was stated before by Morgner et al [13]for UPS and MIES measurements and is con® rmed by our experimental data.…”
Section: Formamide and Benzyl Alcoholcontrasting
confidence: 77%
See 2 more Smart Citations
“…In previous studies on polar solvents, binary mixtures and salt solutions [6][7][8][9] we have never encountered an effect of this voltage on our spectra, apart from a smooth change of relative intensity as a function of electron energy. However, a recent study on a phospholipid monotayer [10] demonstrated the effect of an inhomogeneous electric field on the motion of lipid molecules within the surface layer on a time scale of the order of several seconds.…”
Section: Experimental Methodsmentioning
confidence: 54%